Applied Linguistics: Current Trends and Prospects (International Conference in Sofia University, Bulgaria, 2023) - Irena Dimova (Slavia Meridionalis, 2025)
Applied Linguistics: Current Trends and Prospects (International Conference in Sofia University, Bulgaria, 2023) This review gives an account of an international conference entitled Applied Linguistics: Current Trends and Prospects, which took place on the 18th and 19th of November 2023 at Sofia University “St. Kliment Ohridski” in Bulgaria. It was organized by the Department of English and American Studies at the Faculty of Classical and Modern Philology of Sofia University and was aimed at celebrating both the 135th anniversary of Sofia University and the 95th anniversary of the Department of English and American Studies at Sofia University. It provided a forum for the discussion of current trends and prospects in the field of applied linguistics, bringing together scholars from universities in both Bulgaria and abroad.   Lingwistyka stosowana: aktualne trendy i perspektywy (Międzynarodowa konferencja na Uniwersytecie Sofijskim, Bułgaria, 2023) Niniejsza recenzja przedstawia relację z międzynarodowej konferencji pt. „Lingwistyka stosowana: aktualne trendy i perspektywy”, która odbyła się 18 i 19 listopada 2023 roku na Uniwersytecie Sofijskim im. św. Klimenta Ochrydzkiego w Bułgarii. Konferencja została zorganizowana przez Katedrę Anglistyki i Studiów Amerykanistycznych Wydziału Filologii Klasycznej i Nowoczesnej Uniwersytetu Sofijskiego i miała na celu uczczenie zarówno 135. rocznicy powstania Uniwersytetu Sofijskiego, jak i 95. rocznicy istnienia Katedry Anglistyki i Studiów Amerykanistycznych na tym uniwersytecie. Stanowiła forum dyskusji na temat aktualnych trendów i perspektyw w dziedzinie lingwistyki stosowanej, gromadząc naukowców z uniwersytetów zarówno z Bułgarii, jak i zagranicy.